The influence of ethnicity and glucose tolerance status on subjective hunger sensations and prospective food intake in overweight and obese Asian and European Australians. (November 2017) - Muhardi, Leilani; Zhao, Yun; Solah, Vicky; Fyfe, Susan; Soares, Mario J.
Abstract: Aims: To examine the influence of ethnicity and glucose tolerance status on subjective sensations and food intake in overweight/obese Asian and European Australians. Methods: 18 Asians and 26 Europids were classified as normal glucose tolerance (NGT) and impaired glucose tolerance (IGT) based on serial measures of finger-prick glucose following an oral glucose tolerance test (OGTT). Subjective sensations of hunger and satiety were measured before and every 15 min after the OGTT using a visual analogue scale (VAS). Food intake was measured covertly from consumption of a buffet style lunch and from self-maintained 24 h food records. All serial measurements were converted into total area under the curve (TAUC) and comparisons adjusted for age, fat and fat-free mass. Results: There was a significant difference interaction between ethnicity (ETH) and glucose tolerance (GTT) for subjective fullness, desire for food and prospective food intake. IGT Asians had significantly greater sensations of fullness, but lesser prospective food and desire to eat, as compared to other groups. However there were no differences in calorie and macronutrient intake at buffet lunch or over 24-h. Conclusion: Interactions between ethnicity and glucose tolerance status in subjective sensations did not transcribe to differences in prospective food intake.